Breeding Biology of the Grey Mullet, Valatnugil cunnesius from the Ashtamudi Estuary, Southwest Coast of India - K., Krishnakumar; N., Balakrishnan Nair (Fishery Technology, 2025)
Breeding biology of Valatnugil cunnesius (Val.)/ inhabiting the Ashtamudi estuary along the southwest coast of India, was studied in detail. Sixmaturity stages viz., immature, maturing-I, maturing-II, mature, oozing and spent were identified. Relatively higher Gonado-somatic indices were observed during July to December. Results revealed that V. cunnesius in the Ashtamudi waters has a prolonged spawning season which extends from July to December. The size at first maturity for males is around 139 mm and for females around 148 mm (total length). The sex-ratio of males to females was 1:1.5.